2003
DOI: 10.1242/dev.00360
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog signalling is required for correct anteroposterior patterning of the zebrafish otic vesicle

Abstract: Currently, few factors have been identified that provide the inductive signals necessary to transform the simple otic placode into the complex asymmetric structure of the adult vertebrate inner ear. We provide evidence that Hedgehog signalling from ventral midline structures acts directly on the zebrafish otic vesicle to induce posterior otic identity. We demonstrate that two strong Hedgehog pathway mutants, chameleon (con tf18b ) and slow muscle omitted (smu b641 ) exhibit a striking partial mirror image dupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
122
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 63 publications
(135 citation statements)
references
References 82 publications
12
122
1
Order By: Relevance
“…Significant percentages resulted in duplicated inner ears, with two anterior or two posterior halves fused as if mirror images. These percentages were much higher than was ever seen with the amphibian rotation studies (Yntema, 1955) or even the zebrafish Hh signaling pathway mutants (Hammond et al, 2003). Labeled grafting experiments confirmed that the regenerated tissue was from the remaining placode and not surrounding tissues.…”
Section: Introductionmentioning
confidence: 66%
See 4 more Smart Citations
“…Significant percentages resulted in duplicated inner ears, with two anterior or two posterior halves fused as if mirror images. These percentages were much higher than was ever seen with the amphibian rotation studies (Yntema, 1955) or even the zebrafish Hh signaling pathway mutants (Hammond et al, 2003). Labeled grafting experiments confirmed that the regenerated tissue was from the remaining placode and not surrounding tissues.…”
Section: Introductionmentioning
confidence: 66%
“…In zebrafish, Hh signaling is required for posterior identity; when it is inhibited, anterior structures are duplicated posteriorly (Hammond et al, 2003). Hip is a vertebrate-specific inhibitor of Hh signaling that was discovered in mice (Chuang and McMahon, 1999;Koebernick et al, 2003).…”
Section: Blocking Hedgehog Signaling Results In Mirror Anterior Duplimentioning
confidence: 99%
See 3 more Smart Citations